High Cadmium Levels in Individuals with Depressive Mood: Re-sults from the 2008-2013 Korean National Health and Nutrition Survey - In Cheol Hwang; Hong Yup Ahn (Tehran University of Medical Sciences, 2021)
Background: The relationship between cadmium (Cd) exposure and depression remains unclear. This nationwide study aimed to compare the levels of blood Cd with the presence of depressive mood in Korean adults. Methods: From the 2008-2013 Korea National Health and Nutrition Examination Survey, 10,968 individuals over 20 yr old were identified. Data on demographics, health behaviors, depressive mood, and blood Cd (B-Cd) levels were used in the analysis. Estimated levels of B-Cd were drawn from multivariate regression models. Results: Higher age-adjusted B-Cd levels were noted among women, rural residents, people who have a low economic or educational status, smoke currently, drink frequently, or have depressive mood than the counterpart groups. In fully adjusted models, men with depressive mood exhibited significantly higher B-Cd levels than those without depressive mood, and these levels were strongly mediated by smoking status. Conclusion: Our results suggest a need for Cd accumulation screening among individuals with depressive mood.